Paracoccidioidomycosis in an Elderly Simulating Cholangiocarcinoma - Guerra, Isabel (2021)
Paracoccidioidomycosis, the most prevalent deep mycosis in Latin America, is caused by dimorphic species of the genus Paracoccidioides, affects predominantly male rural workers between 30-50 years of age and is an important cause of morbidity and mortality. It can present in two clinical forms: acute/subacute or chronic. In rare cases paracoccidioidomycosis may simulate neoplasia and must be considered as a differential diagnosis of intra-abdominal tumors in endemic areas. We report an exuberant case of subacute paracoccidioidomycosis in an elderly lady, although it is more frequent in the juvenile form. Multiple facial skin lesions were associated with a wasting syndrome and extensive adenopathy including in the hepatic area, causing bile duct dilatation simulating a cholangiocarcinoma. Skin histopathology was diagnostic and antifungal treatment allowed complete resolution of cutaneous and systemic lesions, thus highlighting the merit of the dermatologist, who was fundamental for the conclusive diagnosis and institution of specific therapy, resulting in a favorable outcome.